The Meanings of Advertisements in Palopo Pos Newspaper (A Semantical Analysis) - Muli Umiaty Noer; Chuzaimah Chuzaimah; Tri Asta Handayani (Tamaddun Life, 2017)
This research aimed at finding out the kinds of advertisement in Palopo Pos Newspaper and the meaning of advertisement in Palopo Pos Newspaper. The method used in this research was descriptive qualitative method. The source of data in this research was the Newspaper, named Palopo Pos Newspaper. The data are collected from the advertisement in Palopo Pos Newspaper from January until December 2013 edition and 2014 edition. In analyzing the data, the writer used semantical analysis by using Geoffrey Leech’s Theory. It aimed at finding out the kinds and the meaning of advertisement in Palopo Pos Newspaper, then the writer analyzed and explain the data from the newspaper. The result of this research showed that there were six kinds of advertisement was found. There were costumer, financial, business, trade, recruitment and retail advertisement.Whereas there were seven kinds of meaning in advertisement was found. There were social, affective, connotative, conceptual, collocative, thematic and reflected meaning. The purpose of this research is to give understanding about the kinds and the meaning of advertisement used semantical analysis by using Geoffrey Leech’s Theory to readers or the next researchers who would like to know and research more about it.